Ghrelin receptor inverse agonists as a novel therapeutic approach against obesity‐related metabolic disease. Issue 12 (13th July 2017) - Abegg, Kathrin; Bernasconi, Lara; Hutter, Melanie; Whiting, Lynda; Pietra, Claudio; Giuliano, Claudio; Lutz, Thomas A.; Riediger, Thomas
Abstract : Aims: Ghrelin is implicated in the control of energy balance and glucose homeostasis. The ghrelin receptor exhibits ligand‐independent constitutive activity, which can be pharmacologically exploited to induce inverse ghrelin actions. Because ghrelin receptor inverse agonists (GHSR‐IA) might be effective for the treatment of obesity‐related metabolic disease, we tested 2 novel synthetic compounds GHSR‐IA1 and GHSR‐IA2. Materials and Methods: In functional cell assays, electrophysiogical and immunohistochemical experiments, we demonstrated inverse agonist activity for GHSR‐IA1 and GHSR‐IA2. We used healthy mice, Zucker diabetic fatty (ZDF) rats and diet‐induced obese (DIO) mice to explore effects on food intake (FI), body weight (BW), conditioned taste aversion (CTA), oral glucose tolerance (OGT), pancreatic islet morphology, hepatic steatosis (HS), and blood lipids. Results: Both compounds acutely reduced FI in mice without inducing CTA. Chronic GHSR‐IA1 increased metabolic rate in chow‐fed mice, suppressed FI, and improved OGT in ZDF rats. Moreover, the progression of islet hyperplasia to fibrosis in ZDF rats slowed down. GHSR‐IA2 reduced FI and BW in DIO mice, and reduced fasting and stimulated glucose levels compared with pair‐fed and vehicle‐treated mice. GHSR‐IA2‐treated DIO mice showed decreased blood lipids. GHSR‐IA1 treatment markedly decreased HS in DIO mice. Conclusions: Our study demonstrates therapeutic actions of novel ghrelin receptor inverse agonists, suggesting a potential to treat obesity‐related metabolic disorders including diabetes mellitus.